The Effect of the Ranking One Game Model on Interest in Learning History of Class XI IPS Students at SMA Negeri 5 Banda Aceh. - Fanisa, Dian; Zulfan, Zulfan; Kesuma, T. Bahagia (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2024)
This research aims to determine the effect of the ranking one game model on the interest in learning history of class XI IPS students at SMA Negeri 5 Banda Aceh. This research uses a quantitative approach with a true experimental design research type, in the form of a posttest only control design. The population in this research is all students of class XI IPS SMA Negeri 5 Banda Aceh which consists of 4 classes with 114 students. The sample in this study was class XI IPS-4 students consisting of 28 students as the control class and class XI IPS-3 students consisting of 28 students as the experimental class. The data collection techniques used are observation, questionnaires and documentation. The data analysis technique on the observation sheet is using the total score formula for the observation results and on the questionnaire sheet using normality, homogeneity and paired sample t-test hypothesis testing. Based on the results of the observation sheet in the experimental class, it was found that student interest in learning was 88% in the very good category and in the control class it was 83% in the good category. Through the paired sample t-test on SPSS ver 22, sig = 0.000 0.05 with tcount = 6.920 ttable 1.703 at the significance level = 5% (0.05), then Ho is rejected and Ha is accepted or there is an effect of the game model ranking one for the interest in studying history of class XI IPS students at SMA Negeri 5 Banda Aceh.